A career ladder professional development approach to employee engagement for technicians in academic veterinary medicine - Fletcher, Kendra; Paton, Valerie Osland; Jones, Stephanie J.; Levine, Jonathan M.; Kerwin, Sharon C.; Eckman, Stacy (Frontiers in Veterinary Science, 2025)
IntroductionThis qualitative case study explored how a career ladder advancement program, with programmatic changes based on employee input and programmatic evaluation, related to employee engagement among veterinary technicians in a veterinary medical teaching hospital. While research regarding the implementation and outcomes of career ladders exists in multiple healthcare, private industry, and higher education contexts, there is no research pertaining directly to Veterinary Technicians within a revenue-generating organization affiliated with an institution of higher education, limiting the ability to address veterinary technician retention.MethodsFramed using Kahn’s theory of employee engagement, the study involved semi-structured interviews of 17 veterinary technicians to ascertain contributors and barriers to employee engagement through a structured career ladder program for promotion.ResultsThe study found that value and communication, patient care and teaching, and professional growth and development all contributed to engagement. In addition, organizational structure and perspective (goals, strategies and approach), as well as lack of support, were the key barriers to employee engagement.DiscussionKey recommendations from the study are building robust advancement programs, adopting a meaningful approach to communication, consider staffing and workload needs, and directly address issues of climate and culture within the organization.